2023
DOI: 10.3390/ijms24032169
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Molecular Response to High-Fat Diet Differs between Rats with Constitutionally High and Low Serotonin Tone

Abstract: Maintaining energy balance is a complex physiological function whose dysregulation can lead to obesity and associated metabolic disorders. The bioamine serotonin (5HT) is an important regulator of energy homeostasis, with its central and peripheral pools influencing energy status in opposing ways. Using sublines of rats with constitutionally increased (high-5HT) or decreased (low-5HT) whole-body 5HT tone, we have previously shown that under standard diet constitutionally higher 5HT activity is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…In our previous research, we have used the WZ-5HT rat model to investigate the impact of interindividual differences in 5HT tone on the net energy balance of the organism. We have shown that constitutively higher 5HT activity is associated with increased body adiposity and impaired glucose homeostasis [44], but, interestingly, with less adverse metabolic outcomes in response to a high-fat diet [45]. Baseline measurements have also shown that high-5HT animals have a lower amount of BAT [46] and a lower skin temperature above BAT [45], suggesting that differences in thermogenesis contribute to differential metabolic health observed between the 5HT sublines.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our previous research, we have used the WZ-5HT rat model to investigate the impact of interindividual differences in 5HT tone on the net energy balance of the organism. We have shown that constitutively higher 5HT activity is associated with increased body adiposity and impaired glucose homeostasis [44], but, interestingly, with less adverse metabolic outcomes in response to a high-fat diet [45]. Baseline measurements have also shown that high-5HT animals have a lower amount of BAT [46] and a lower skin temperature above BAT [45], suggesting that differences in thermogenesis contribute to differential metabolic health observed between the 5HT sublines.…”
Section: Introductionmentioning
confidence: 80%
“…We have shown that constitutively higher 5HT activity is associated with increased body adiposity and impaired glucose homeostasis [44], but, interestingly, with less adverse metabolic outcomes in response to a high-fat diet [45]. Baseline measurements have also shown that high-5HT animals have a lower amount of BAT [46] and a lower skin temperature above BAT [45], suggesting that differences in thermogenesis contribute to differential metabolic health observed between the 5HT sublines. In the present study, we aimed to further investigate the interplay between endogenous 5HT tone and BAT functioning by comparatively analyzing the BAT thermogenic activity (at functional and molecular levels) of 5HT sublines in response to specific physiological (cold exposure) or pharmacological (β 3 -adrenergic agonist) challenges (Figure 1).…”
Section: Introductionmentioning
confidence: 80%
“…315−317 However, continued HFD consumption has been associated with triggering depression in humans and animal models. 318 This corresponds with a drop in the synthesis and levels of 5-HT, 319,320 while simultaneously increasing the expression of genes responsible for the fatty acid desaturase FADS1 and FADS2. 321 A study by Jaddoa and colleagues presents indirect evidence of 5-HT's role in regulating lipid enzymes in the brain.…”
Section: Acsmentioning
confidence: 99%
“…Acute high-fat diets (HFD) are highly satisfying and stimulate an immediate rise in monoaminergic activity within the brain’s reward system. However, continued HFD consumption has been associated with triggering depression in humans and animal models . This corresponds with a drop in the synthesis and levels of 5-HT, , while simultaneously increasing the expression of genes responsible for the fatty acid desaturase FADS1 and FADS2 …”
Section: Serotonin Effects On Lipid Regulationmentioning
confidence: 99%
“…In addition, Čičin-Šain and colleagues [23] explored the metabolic response of high and low serotonin tones in rats exposed to an obesogenic diet. Rat sublines with constitutionally low serotonin levels were more subjected to major metabolic alterations, insulin resistance and body weight gain.…”
Section: A Commemorative Issue In Honour Of Rudolf Virchowmentioning
confidence: 99%